2014
DOI: 10.1146/annurev-immunol-032713-120231
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-Stimulated Genes: A Complex Web of Host Defenses

Abstract: Interferon-stimulated gene (ISG) products take on a number of diverse roles. Collectively, they are highly effective at resisting and controlling pathogens. In this review, we begin by introducing interferon (IFN) and the JAK-STAT signaling pathway to highlight features that impact ISG production. Next, we describe ways in which ISGs both enhance innate pathogen-sensing capabilities and negatively regulate signaling through the JAK-STAT pathway. Several ISGs that directly inhibit virus infection are described … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

48
2,620
0
42

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 2,568 publications
(2,710 citation statements)
references
References 248 publications
(239 reference statements)
48
2,620
0
42
Order By: Relevance
“…In response to this binding signal, the JAK‐STAT pathway is activated, leading to transcriptional up‐regulation of the ISGs (Ivashkiv & Donlin, 2014; Schneider et al , 2014). Therefore, to show that the up‐regulated ISGs upon HNRNPC knock‐down depend on the interferon signaling cascade, we used an IFNβ antibody, an IFNAR2 blocking antibody, and the JAK‐STAT inhibitor ruxolitinib to block the interferon signaling pathway at different levels.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In response to this binding signal, the JAK‐STAT pathway is activated, leading to transcriptional up‐regulation of the ISGs (Ivashkiv & Donlin, 2014; Schneider et al , 2014). Therefore, to show that the up‐regulated ISGs upon HNRNPC knock‐down depend on the interferon signaling cascade, we used an IFNβ antibody, an IFNAR2 blocking antibody, and the JAK‐STAT inhibitor ruxolitinib to block the interferon signaling pathway at different levels.…”
Section: Resultsmentioning
confidence: 99%
“…IFNβ can be expressed in most of the cell types upon invasion of microbes and sensing of the microbial components by the pattern recognition receptors (PRRs; Nagarajan, 2011; Schneider et al , 2014). In addition, the type I interferon production can also be activated by the PRRs sensing the endogenous nucleic acids under stress conditions such as radiation, autoimmune disease, and cancer (West et al , 2015; Roers et al , 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, a recent study with human cells reported that activation of the IFN pathway through MAVS led to inhibition of RISC‐mediated cleavage and repression activities (Seo et al , 2013). Alternatively, the sequence‐specific hallmark of dsRNAi might be masked by sequence‐unspecific effects resulting from the activity of ISGs, which cause a dsRNA‐dependent shutdown in cellular protein synthesis and/or induce cell death (Samuel, 2001; Schneider et al , 2014). Irrespective of mechanism, our data suggest that RNAi might be especially important in conditions of limited IFN induction or in cellular niches that possess a reduced IFN response pathway.…”
Section: Discussionmentioning
confidence: 99%
“…In the IFN response, those RNAs are generally detected by members of the RIG‐I family of pattern recognition receptors, which then bind to the mitochondrial adaptor MAVS to initiate a signalling cascade that culminates in the production and secretion of IFN‐β and IFN‐α, among others (Goubau et al , 2013). IFN‐α and IFN‐β bind to the IFN receptor (IFNAR), which signals to induce hundreds of interferon‐stimulated genes (ISGs) that work to increase antiviral resistance (Samuel, 2001; Goubau et al , 2013; Schneider et al , 2014). For example, the ISG protein kinase R (PKR), when activated by viral dsRNA, phosphorylates the alpha subunit of the protein synthesis initiation factor‐2, causing inhibition of both viral and cellular translation (Pindel & Sadler, 2011).…”
Section: Introductionmentioning
confidence: 99%